2016
DOI: 10.1007/s00464-016-4813-1
|View full text |Cite
|
Sign up to set email alerts
|

Peroral endoscopic myotomy for esophageal achalasia: outcomes of the first over 100 patients with short-term follow-up

Abstract: Our results confirm the efficacy of POEM in a large patient series and support POEM as one of the first-line achalasia therapies in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
44
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 31 publications
8
44
1
Order By: Relevance
“…Our median operation time was 73.0 minutes (range 39 – 184 minutes) whereas previous studies reported a range of 22.9 – 148 minutes 22 23 24 25 . We observed a significant reduction in symptoms: (median [range], preoperative Eckardt score 6 2 3 4 5 6 7 8 9 10 11 vs. postoperative 0 [0 – 4]; P  < 0.001), with a significant reduction in IRP (median [range], preoperative 26.0 mmHg [2.3 – 75] vs. postoperative 9 mmHg [0.1 – 23.8]).…”
Section: Discussionmentioning
confidence: 54%
“…Our median operation time was 73.0 minutes (range 39 – 184 minutes) whereas previous studies reported a range of 22.9 – 148 minutes 22 23 24 25 . We observed a significant reduction in symptoms: (median [range], preoperative Eckardt score 6 2 3 4 5 6 7 8 9 10 11 vs. postoperative 0 [0 – 4]; P  < 0.001), with a significant reduction in IRP (median [range], preoperative 26.0 mmHg [2.3 – 75] vs. postoperative 9 mmHg [0.1 – 23.8]).…”
Section: Discussionmentioning
confidence: 54%
“…With recent advances in endoscopic treatment techniques and devices, Inoue et al[9] have developed peroral endoscopic myotomy, in which the myotomy is performed through a submucosal tunnel. Excellent long-term outcomes after POEM have been reported[1,2], and POEM is expected to become a first-line therapy for achalasia requiring surgical intervention. However, some major perioperative adverse events from POEM have also been reported, with mucosal penetration being one of the most dangerous adverse events[1,2,5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Excellent long-term outcomes after POEM have been reported[1,2], and POEM is expected to become a first-line therapy for achalasia requiring surgical intervention. However, some major perioperative adverse events from POEM have also been reported, with mucosal penetration being one of the most dangerous adverse events[1,2,5,6]. Mucosal penetration during POEM occurs at a rate ranging from 4.2%-17.3% depending on the study[1,2,5,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations